Evaluation of a PCR-RFLP- ITS2 assay for discrimination of Anopheles species in northern and western Colombia - Cienfuegos, Astrid V. (2011)
Anopheles mosquitoes are routinely identified using morphological characters of the female that often lead to misidentification due to interspecies similarity and intraspecies variability. The aim of this work was to evaluate the applicability of a previously developed PCR-RFLP-ITS2 assay for accurate discrimination of anophelines in twelve localities spanning three Colombian malaria epidemiological regions: Atlantic Coast, Pacific Coast, and Uraba-Bajo Cauca-Alto Sinu Region. The evaluation of the stability of the PCR-RFLP patterns is required since variability of the ITS2 has been documented and may produce discrepancies in the patterns previously reported. The assay was used to evaluate species assignation of 939 mosquitoes identified by morphology. Strong agreement between the morphological and molecular identification was found for species An. albimanus, An. aquasalis, An. darlingi and An. triannulatus s.l. (p ≥ 0.05, kappa=1). However, disagreement was found for species An. nuneztovari s.l., An. neomaculipalpus, An. apicimacula and An. punctimacula (p ≤ 0.05; kappa ranging from 0.33–0.80). The ITS2-PCR-RFLP assay proved valuable for discriminating anopheline species of northern and western Colombia, especially those with overlapping morphology in the Oswaldoi Group.